Robotic Search and Rescue using Human Detection System - et. al., Golande Avinash L, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this Technological advancement period, advanced construction improvements lead the formation of skyscrapers and homes which expanded the dangers of losing life because of natural and manmade catastrophes. In this system, we are proposing a radio-controlled bot that can identify live human beings from which are in the inaccessible region. Python libraries are used in Raspberry Pi microcontroller having Camera module to catch pictures of objects around it. This paper discusses about the mentioned system. The project takes live image samples and sends it to a network where this images can be accessed through a device. This images can be used for human detection. PIR sensor is used for the detection of human being trapped under debris. Whenever a human is detected the bot will send GPS co-ordinates to the device.